Respuesta :
the correct answer is B) x = 1.
From the first equation, we have y = 2x - 1.
Substituting this into the second equation, we get 2x - 1 = x².
Rearranging the equation, we have x² - 2x + 1 = 0.
Factoring the equation, we have (x - 1)(x - 1) = 0.
Therefore, the only value of x that satisfies the system of equations is x = 1.
So, the correct answer is B) x = 1.
From the first equation, we have y = 2x - 1.
Substituting this into the second equation, we get 2x - 1 = x².
Rearranging the equation, we have x² - 2x + 1 = 0.
Factoring the equation, we have (x - 1)(x - 1) = 0.
Therefore, the only value of x that satisfies the system of equations is x = 1.
So, the correct answer is B) x = 1.